Рефлексия исторического фона в шпионских романах Грэма Грина - Норец, М.В. (Культура народов Причерноморья, 2013)
Данная работа посвящена анализу творчества Валентина Уильямса в контексте эволюции жанра английского шпионского романа. В исследовании предпринимается попытка проанализировать развитие жанра шпионского романа в начале ХХ века, в период Второй мировой войны, в контексте происходящих исторических событий, с учётом факта причастности автора тем или иным образом к деятельности британских спецслужб. Автор анализирует творчество Грэма Грина с точки зрения его жанровой идентификации и его дальнейшего влияния на развитие жанра английского шпионского романа в целом. Предлагается рассмотреть главных героев характеризующих основные шпионские романы Грэма Грина. Дана робота присвячена аналізу творчості Валентина Уильямса в контексті еволюції жанру англійського шпигунського роману. У дослідженні здійснюється спроба проаналізувати розвиток жанру шпигунського роману на початку ХХ століття, у період Другої світової війни, у контексті історичних подій, що відбуваються, з урахуванням факту причетності автора тим або іншим способом до діяльності британських спецслужб. Автор аналізує творчість Грема Гріна з точки зору його жанрової ідентифікації і його подальшого впливу на розвиток жанру англійського шпигунського роману в цілому. Пропонується розглянути головних героїв, що характеризують основні шпигунські романи Грема Гріна. The work is dedicated to the analysis of Graham Greens’ works in the context of English spy novel evolution. In the investigation presented the attempt to analyze the forming of the spy novel genre at the beginning of the XX th century, during the period of the Second World War is made in the context of the historical events taking place at that period of time, taking into account the fact of belonging the author to the Great Britain State Intelligence service. The author analyzes Grahams’ works from the point of view of its genre identification and its further influence on the development of the English spy novel genre in general. The main protagonists characterizing his spy novels are under consideration. His spy novels belong to the spy novel genre because they are united be genre dominant. The plot of his novels take place during the period of the Second World War and this fact strengthens the dramatic atmosphere of the novels, the protagonists have not yet transformed into the professional agents or spies, nevertheless they have to make a deal with their conscience, get precious skills of the spy activities at the front and at once. Although they are very comforting inside, they are people who suffer much from all the horrors of war, feeling the inescapable guilt before themselves and the motherland.